Surface activation of CNT Webs towards layer by layer assembly of biosensors. Issue 9 (28th January 2016) - Musameh, Mustafa; Huynh, Chi P.; Hickey, Mark; Kyratzis, Ilias Louis
Abstract : Several surface activation methods such as chemical, electrochemical and plasma have been used for enhancing the electrochemical performance of carbon based electrodes for various applications. Abstract : Several surface activation methods such as chemical, electrochemical and plasma have been used for enhancing the electrochemical performance of carbon based electrodes for various applications. However, some of these surface activation methods may not be useful depending on the chemical and physical properties of the activated surface. Herein we investigate the surface activation of carbon nanotube (CNT) webs by electrochemical and plasma techniques to enhance their electrochemical performance and enable the fabrication of a biosensor using the layer-by-layer (LBL) approach. The pretreated CNT webs were characterized by SEM, TEM, Raman, XPS and electrochemical methods. TEM images and Raman analysis showed an increase in the level of surface defects upon pretreatment with higher number of defects after electrochemical pretreatment. XPS analysis showed an increase in the level of oxygen functional groups after pretreatment (4 to 5 times increase) which resulted in enhanced water wettability especially for plasma pretreated CNT webs. The pretreated CNT web electrodes also showed an enhanced electrochemical activity towards the oxidation and reduction of different redox probes with higher sensitivity for the electrochemically pretreated CNT web electrode that was accompanied by a higher level of noise in amperometric measurements. A highly linear response was obtained for the untreated and the electrochemically pretreated CNT web electrodes towards the amperometric detection of NADH ( R 2 of 0.9996 and 0.9986 respectively) while a non-linear response was observed for the plasma pretreated CNT web electrode ( R 2 of 0.8538). The pretreated CNT web electrodes enabled the fabrication of a LBL biosensor for alcohol detection with highest operational stability obtained for the plasma pretreated CNT web surface.